Pengaruh Budaya Organisasi Terhadap Psychological Well Being, Job Involvement Dan Kinerja Guru SMA Negeri Di Wilayah Gerbangkertasusila Provinsi Jawa Timur - Fanani, * (Program Doktor Ilmu Ekonomi, 2014)
This study examines whether the organization culture, psychological well being, job involvement have an influence on the performance of teachers in the region gerbangkartasusila, respondents surveyed in this study were the teachers of Senior high school in the region; with a sample of 220 teachers. With good empirical analysis using individual micro data is cross Seccion survey conducted for the teachers of Senior high school in the region as well as the calculation of, Structural Equation Modelling (SEM) which were processed using Amos 20 version. Result of this study get some conclusion that organizational culture (X) turns significant and positive impact on psychological well being (Z1) teachers of Senior high school in the region Gerbangkartasusila. Organization culture (X) turns out significant and positive impact on job involvement (job involvement) in the region are the teachers of Senior high school (Z2). Organizational culture (X) turns significant and positive impact on performance (Y) Senior High School teachers in the region Gerbangkartasusila. Psychological well being (Z1) turns significant and positive impact on job involvement (job involvement) at teachers Senior high school in the region. Psychological well being significant and positive impact on the performance of school teachers of Senior high school (Z1) in Gerbangkartasusila. Involvement of work (job involvement) (Z2) significant and positive impact on the performance of the teachers at Senior high school in region Gerbangkartasusila East Java (Y). So the results of this study provide a clear evidence of the empirical findings and strongly suggests that the performance of the teachers of Senior high school Gerbangkartasusila in East Java is strongly influenced by the culture of the organization and the level of the teachers' well being as well as the level of involvement the teachers work.Key Word : Organization Culture, Psychological Well Being, Job Involvement. Perfor-mance